EFEKTIVITAS IKLAN PADA MEDIA SOSIAL INSTAGRAM KOJAMA SHOP DENGAN PENDEKATAN AIDA MODEL - Shilla Novira Pertiwi; Pandi Pardian; Lucyana Trimo; Agriani Hermita Sadeli (Universitas Galuh Ciamis, 2021)
Many parties such as business people have used technological developments to facilitate their marketing activities. The technology that is often used in marketing, especially in the promotional aspect, is social media instagram. One of the business players who use Instagram as a promotional media is Kojama Shop, an online shop that sells avocado butter and other local fruits. This report is written with objective of knowing the advertising effectiveness of social media instagram Kojama Shop. The sampling technique used to research was convenience sampling on Kojama Shop active followers. This research used AIDA model method which consists of four dimensions; attention, interest, desire, and action. The results prove that the advertisement on Kojama Shop instagram is considered very effective with a value of 4.337 for the attention dimension, 4.26 for the interest dimension, and 4.277 for the desire dimension. Meanwhile, it was considered effective with a value of 4.117for the action dimension. The improvement recommendations for the action dimension are to develop and provide innovations in promotional methods to increase consumer confidence in making purchases. The results of this study also prove that the overall value of the AIDA is considered very effective with an AIDA Rate value of 4.248.